Developing Religious Character-Based Thematic Textbooks for Elementary School - Muhammad Syabrina; Sulistyowati Sulistyowati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The development of thematic textbooks at the elementary school level with the basis of religious characters has been developed based on the facts in the field that thematic textbooks are very lacking, especially for students studying at Islamic-based primary level schools by accommodating thematic and character learning at once. The result of this development product is a thematic textbook at the elementary school level based on religious characters for students in class 4 elementary schools on the theme 9 sub-theme 1 in accordance with integrative thematic learning, namely Makananku Sehat dan Bergizi. This development design model adopted Dick and Lou Carey. The results at the product validation stage were as follows, 1) the material expert gave a value of 85.00%, 2) the linguist gave a score of 85.00%, 3) the media and learning design expert gave a value of 86.66%, 4) the learning practitioner or the class 4 homeroom teacher gave a value of 86.66%. The results of the product trials are as follows, 1) individual trials give a value of 90.00%, 6) small group trials get a value of 91.67%, 7) field trials get a value of 93.29%. While the t-test of religious character through the pre-test showed an average acquisition of 2.41 or 60.29% and a post-test score of 3.06 or 76.47% in character qualifications that have been seen or cultured. The difference in value increased by 0.65 or 16.18%.